Clinical Practice Guide for Pain Management in Oncological Patients from a Network of Private Clinics, Lima - Peru - Berenguel, María (2022)
Background: The article summarizes the process of elaboration of the Clinical Practice Guide (CPG) for the management of cancer patients. The elaboration process was carried out with the participation of a multidisciplinary team of assisting physicians, methodologists and various external reviewers (specialists with mastery in the methodology and the subject). The prioritization of PICO questions was carried out by the GPC Elaboration Group (GEG), after which 05 PICO questions were concluded. To answer the questions, a systematic search of CPGs, systematic reviews and primary studies was carried out. The “GRADE” methodology and the guidelines of national regulations were used to formulate recommendations. Twelve recommendations were made (ten strong and two weak), 5 points of good clinical practice, 04 consensus tables on the management of cancer pain. The topics that covered the recommendations for pain management in cancer patients were: early treatment intervention, analgesic therapy in mild to moderate pain and moderate to severe pain, neuropathic pain and non-pharmacological interventions.